Cuestiones de jurisdicción internacional en torno a la aplicación privada del Derecho antitrust: forum shopping y demandas torpedo - Suderow, Julia (CUADERNOS DE DERECHO TRANSNACIONAL, 2010)
The support to the private enforcement of Competition Law entails an increase of the actions for damages based on infringements of Competition Law. Due to the transnational nature of many infringements, the actions based on such infringements can also be carried out in several jurisdictions. In this sense; the involved parties use the rules of international jurisdiction and lis pendens as a defence strategy against potential claims. This essay analyses the International Private Law rules applicable to these disputes about the jurisdiction of the affected courts and the problems that are currently arising and possible solutions proposed by the courts themselves or by the doctrine.